Language as an Agent of Change: Promoting Gender Fairness - Montano, Mary Rose; Opeña, Anna Rhea C.; Miranda, Maria Mylin S. (Technium Social Sciences Journal, 2024)
This research explores the complex dynamics of gendered language usage in an effort to provide guidance for language-based initiatives that advance gender equality. The study includes a number of goals, such as determining how frequently gendered words are used, analyzing inclusive language policies' effectiveness and presence, learning about respondents' opinions about gendered language, and finding barriers to the adoption of gender-inclusive terminology. The researcher used a Likert scale to analyze the findings after conducting a quantitative survey with 118 students from the City College of Calamba's Arts and Sciences Department. The results show that respondents were mostly in agreement with the negative effects of gendered language in media and advertising, as well as the difficulties in promoting gender-neutral language, especially in media sources. , the study proposes an advocacy project, "Language for Equality: Promoting Gender Fairness," aiming to raise awareness and encourage the use of gender-fair language to combat discrimination and foster gender equality within the college community. This research contributes valuable insights to the ongoing discourse on language as a catalyst for transformative societal change. Limitations, however, include the possible influence of social desirability bias and the distinctive characteristics of the sample. Comprehensive qualitative inquiries, cross-cultural and longitudinal studies, mixed-methods approaches, and evaluations of suggested solutions are among the study directions for the future. It is recommended that media professionals compare educational resources and inclusive language training programs to improve their understanding of gendered language hurdles and practical solutions.